Analytical model for mesh stiffness calculation of spur gear pair with non-uniformly distributed tooth root crack. (August 2016) - Chen, Zaigang; Zhai, Wanming; Shao, Yimin; Wang, Kaiyun; Sun, Guohua
Abstract: Gear tooth crack is likely to happen when a gear transmission train is working under excessive and/or long-term dynamic loads. Its appearance will reduce the effective tooth thickness for load carrying, and thus cause a reduction in mesh stiffness and influence the dynamic responses of the gear transmission system, which enables the possibility for gear fault detection from variations of the dynamic features. Accurate mesh stiffness calculation is required for improving the prediction accuracy of the dynamic features with respect to the tooth crack fault. In this paper, an analytical mesh stiffness calculation model for non-uniformly distributed tooth root crack along tooth width is proposed based on previous studies. It enables a good prediction on the mesh stiffness for a spur gear pair with both incipient and larger tooth cracks. This method is verified by comparisons with other analytical models and finite element model (FEM) in previous papers. Finally, a dynamic model of a gear transmission train is developed to simulate the dynamic responses when cracks with different dimensions are seeded in a gear tooth, which could reveal the effect of the tooth root crack on the dynamic responses of the gear transmission system. The results indicate that both the mesh stiffness and the dynamic response results show that the proposed analytical model is an alternative method for mesh stiffness calculation of cracked spur gear pairs with a good accuracy for both small and large cracks. Highlights: An analytical mesh stiffness calculation model is proposed for cracked spur gears. The model enables accurate mesh stiffness calculation for both small and larger cracks. The effectiveness is verified by comparing with FE results. An 8-DOFs gear dynamic model is developed to reveal the fault vibration features.